2017
DOI: 10.1097/aog.0000000000001895
|View full text |Cite
|
Sign up to set email alerts
|

Single Health System Adherence to 2012 Cervical Cancer Screening Guidelines at Extremes of Age and Posthysterectomy

Abstract: Objectives To estimate the proportion of guideline nonadherent Pap tests in women aged younger than 21 years and older than 65 years and posthysterectomy in a single large health system. Secondary objectives were to describe temporal trends and patient and health care provider characteristics associated with screening in these groups. Methods A retrospective cross-sectional chart review was performed at Fairview Health Services and University of Minnesota Physicians. Reasons for testing and patient and healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 12 publications
1
13
0
2
Order By: Relevance
“… 9 , 10 Prior studies of overuse of screening have predominately focused on testing young women, elderly women, and those who have undergone hysterectomy, and these reports have identified widespread variation in screening patterns and use of testing. 11 , 12 , 13 , 14 The objective of our study was to examine the patterns of cervical cancer screening among average risk women in the US. Specifically, we examined the frequency of testing and follow-up for women with cervical cytologic testing, cotesting, and primary HPV testing among women aged 30 to 65 years.…”
Section: Introductionmentioning
confidence: 99%
“… 9 , 10 Prior studies of overuse of screening have predominately focused on testing young women, elderly women, and those who have undergone hysterectomy, and these reports have identified widespread variation in screening patterns and use of testing. 11 , 12 , 13 , 14 The objective of our study was to examine the patterns of cervical cancer screening among average risk women in the US. Specifically, we examined the frequency of testing and follow-up for women with cervical cytologic testing, cotesting, and primary HPV testing among women aged 30 to 65 years.…”
Section: Introductionmentioning
confidence: 99%
“… 14 , 15 Primary care providers continue to perform routine cervical cancer screening in vast numbers of women older than 65 years in contradiction to these published guidelines. 10 …”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that primary care providers continue to perform cervical cancer screening in women older than 65 years despite clear guidelines to the contrary. 10 This continued activity adds to the financial burden of health care and represents an intervention in older women for which evidence of significant clinical benefit no longer exists. Unnecessary cervical testing consumes primary care provider access while nationwide shortages of these practitioners continue to grow.…”
Section: Introductionmentioning
confidence: 99%
“…Data collection and designation of guideline nonadherent Pap tests in women for whom testing was not indicated have been previously described. 11 In brief, Pap tests performed in women younger than 21 or older than 65 years of age or after hysterectomy between September 1, 2012, and August 31, 2014, were identified through a query of the electronic health record. For women who received more than 1 Pap test during this period, only the first Pap test was included in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…10 Of 3,920 individual women who had at least 1 Pap test between September 2012 and August 2014, 65% of the Pap tests were indicated for the following reasons: cancer surveillance (30%), supracervical hysterectomy (22%), inadequate previous screening (18%), follow-up of a previous abnormal Pap test or high-grade dysplasia (16%), within 6 months of age 21 years (9%), evaluation of postmenopausal bleeding or other abnormal exam finding (5%), immunocompromise (1%), and diethylstilbestrol exposure or other indication (<1%). The remaining 35% of Pap tests (N = 1,398) performed in these screening groups were not indicated per the United States 2012 cervical cancer screening guidelines 11 and form the population for this study. Our previous study looked only at whether the Pap test was indicated and did not examine test outcomes.…”
mentioning
confidence: 99%